Non-technical skills assessments in undergraduate medical education: A focused BEME systematic review: BEME Guide No. 54. (3rd July 2019) - Gordon, Morris; Farnan, Jeanne; Grafton-Clarke, Ciaran; Ahmed, Ridwaan; Gurbutt, Dawne; McLachlan, John; Daniel, Michelle
Abstract: Consensus on how to assess non-technical skills is lacking. This systematic review aimed to evaluate the evidence regarding non-technical skills assessments in undergraduate medical education, to describe the tools used, learning outcomes and the validity, reliability and psychometrics of the instruments. A standardized search of online databases was conducted and consensus reached on included studies. Data extraction, quality assessment, and content analysis were conducted per Best Evidence in Medical Education guidelines. Nine papers met the inclusion criteria. Assessment methods broadly fell into three categories: simulated clinical scenarios, objective structured clinical examinations, and questionnaires or written assessments. Tools to assess non-technical skills were often developed locally, without reference to conceptual frameworks. Consequently, the tools were rarely validated, limiting dissemination and replication. There were clear themes in content and broad categories in methods of assessments employed. The quality of this evidence was poor due to lack of theoretical underpinning, with most assessments not part of normal process, but rather produced as a specific outcome measure for a teaching-based study. While the current literature forms a good starting position for educators developing materials, there is a need for future work to address these weaknesses as such tools are required across health education.